Thermal Processing of Peanut Grains Impairs Their Mimicked Gastrointestinal Digestion While Downstream Defatting Treatments Affect Digestomic Profiles - Prodić, Ivana (Foods, 2019)
Resistance to digestion by digestive proteases represents a critical property of many food allergens. Recently, a harmonized INFOGEST protocol was proposed for solid food digestion. The protocol proposes digestion conditions suitable for all kinds of solid and liquid foods. However, peanuts, as a lipid-rich food, represent a challenge for downstream analyses of the digestome. This is particularly reflected in the methodological difficulties in analyzing proteins and peptides in the presence of lipids. Therefore, the removal of the lipids seems to be a prerequisite for the downstream analysis of digestomes of lipid-rich foods. Here, we aimed to compare the digestomes of raw and thermally treated (boiled and roasted) peanuts, resulting from the INFOGEST digestion protocol for solid food, upon defatting the digests in two different manners. The most reproducible results of peanut digests were obtained in downstream analyses on TCA/acetone defatting. Unfortunately, defatting, even with an optimized TCA/acetone procedure, leads to the loss of proteins and peptides. The results of our study reveal that different thermal treatments of peanuts affect protein extraction and gastric/gastrointestinal digestion. Roasting of peanuts seems to enhance the extraction of proteins during intestinal digestion to a notable extent. The increased intestinal digestion is a consequence of the delayed extraction of thermally treated peanut proteins, which are poorly soluble in acidic gastric digestion juice but are easily extracted when the pH of the media is raised as in the subsequent intestinal phase of the digestion. Thermal processing of peanuts impaired the gastrointestinal digestion of the peanut proteins, especially in the case of roasted samples.